Building Information Modelling Execution Plan (BEP) Conceptual Framework for Design and Build Project - Raduan, Syahirah Mat Sahizol; Brahim, Juliana; Mohd Nordin, Rumaizah; Mohd, Suzila; Poniah, Vignes (Journal of Advanced Research Design, 2025)
The execution of Building Information Modelling (BIM) would require a BIM Execution Plan (BEP), which serves as a guide or reference for contracting parties involved in the BIM project, ensuring its successful implementation. However, the lack of understanding on how BEP should be used has resulted to the improper of BIM implementation. Therefore, this research aims to propose a conceptual framework for the BEP in Design and Build (DB) projects. This research will utilise the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) review methodology. The review has resulted in the proposal of a conceptual framework for the BEP in DB projects, comprising 11 key elements. In summary, this research is expected to enhance the implementation of BEP practices among construction professionals in the BIM execution for DB projects, thus could assist construction professionals to reap full benefit of BIM.